The Prognostic Value of Lymph Nodes Dissection Number on Survival of Patients with Lymph Node-Negative Gastric Cancer. (24th April 2014) - Song, Wu; Yuan, Yujie; Wang, Liang; He, Weiling; Zhang, Xinhua; Chen, Chuangqi; Zhang, Changhua; Cai, Shirong; He, Yulong
Abstract : Objective. The study was designed to explore the prognostic value of examined lymph node (LN) number on survival of gastric cancer patients without LN metastasis. Methods. Between August 1995 and January 2011, 300 patients who underwent gastrectomy with D2 lymphadenectomy for LN-negative gastric cancer were reviewed. Patients were assigned to various groups according to LN dissection number or tumor invasion depth. Some clinical outcomes, such as overall survival, operation time, length of stay, and postoperative complications, were compared among all groups. Results. The overall survival time of LN-negative GC patients was 50.2 ± 30.5 months. Multivariate analysis indicated that LN dissection number ( P < 0.001 ) and tumor invasion depth ( P < 0.001 ) were independent prognostic factors of survival. The number of examined LNs was positively correlated with survival time ( P < 0.05 ) in patients with same tumor invasion depth but not correlated with T1 stage or examined LNs > 30 . Besides, it was not correlated with operation time, transfusion volume, length of postoperative stay, or postoperative complication incidence ( P > 0.05 ) . Conclusions. The number of examined lymph nodes is an independent prognostic factor of survival for patients with lymph node-negative gastric cancer. Sufficient dissection of lymph nodes is recommended during surgery for such population.